Clearance of primary necrotic cells by non-professional phagocytes - Schwegler, Manuela; Wirsing, Anna Maria; Dollinger, Alena J.; Abendroth, Benjamin; Putz, Florian; Fietkau, Rainer; Distel, Luitpold (Biology of the Cell, 2015)
Homotypic internalisation of tumour cells has frequently been observed in tumour tissue sections. Events of non-professional phagocytosis, however, may also occur in normal tissue if the number of dying cells exceeds the phagocytic capacity of professional phagocytes such as macrophages and dendritic cells. The aim of this study was to investigate the molecular background of non-professional phagocytosis of primary necrotic cells by neighbouring tumour cells and normal skin fibroblasts.We demonstrate that homotypic and heterotypic uptake of necrotic cells is a feature common to various cell types. Investigating critical stimuli of necrotic cell clearance we found that non-professional phagocytes require cytoskeleton rearrangement, recognition of phosphatidylserine and GTPase activity of dynamin II, which is normally engaged in endocytosis. Additionally, we have observed an accumulation of adhesion molecule E-cadherin, phosphorylated actin-linker protein ezrin, lysosomal-associated membrane protein 1 and microtubule-associated protein 1 light chain 3 at the site of engulfment. Loss of membrane integrity and an increase in the intracellular level of heat-shock protein 70 in the necrotic cells have also been observed.Our results shed light on the mechanism of necrotic cell removal by tumour cells and normal skin fibroblasts in vitro. It is reasonable to assume that this process has a physiological relevance in inflammation and autoimmune disease in normal tissue as well as in tumours regarding immune cell infiltration. We conclude that necrotic cell clearance by non-professional phagocytes contributes to the phagocytic activity by macrophages and that this process may prevent release of proinflammatory damage-associated molecular pattern molecules.
EVALuna2:18281

Non-professional phagocytosis: a general feature of normal tissue cells - Seeberg, Jacob; Loibl, Monika; Moser, Fabian; Schwegler, Manuela; Büttner-Herold, Maike; Daniel, Christoph; Engel, Felix; Hartmann, Arndt; Schlötzer-Schrehardt, Ursula; Goppelt-Strübe, Margarete; Schellerer, Vera; Naschberger, Elisabeth; et al. (Scientific Reports, 2019)
Non-professional phagocytosis by cancer cells has been described for decades. Recently, non-professional phagocytosis by normal tissue cells has been reported, which prompted us to take a closer look at this phenomenon. Non-professional phagocytosis was studied by staining cultured cells with live-cell staining dyes or by staining paraffin-embedded tissues by immunohistochemistry. Here, we report that each of 21 normal tissue cell lines from seven different organs was capable of phagocytosis, including ex vivo cell cultures examined before the 3rd passage as well as the primary and virus-transformed cell lines. We extended our analysis to an in vivo setting, and we found the occurrence of non-professional phagocytosis in healthy skin biopsies immediately after resection. Using dystrophin immunohistochemistry for membrane staining, human post-infarction myocardial tissue was assessed. We found prominent signs of non-professional phagocytosis at the transition zone of healthy and infarcted myocardia. Taken together, our findings suggest that non-professional phagocytosis is a general feature of normal tissue cells.
CRIS-Team Scopus Importer:2019-08-27

PML-nuclear bodies decrease with age and their stress response is impaired in aged individuals - Wenger, Barbara; Schwegler, Manuela; Brunner, Michaela; Daniel, Christoph; Schmidt, Manfred; Fietkau, Rainer; Distel, Luitpold (BMC Geriatrics, 2014)
Promyelocytic leukemia nuclear bodies (PML-NBs) have been depicted as structures which are involved in processing cell damages and DNA double-strand break repairs. The study was designed to evaluate differences in patients' PML-NBs response to stress factors like a cancerous disease and ionizing radiation exposure dependent on age.In order to clarify the role of PML-NBs in the aging process, we examined peripheral blood monocytes of 134 cancer patients and 41 healthy individuals between 22 and 92 years of age, both before and after in vitro irradiation. Additionally, we analyzed the samples of the cancer patients after in vivo irradiation. Cells were immunostained and about 1600 cells per individual were analyzed for the presence of PML- and ?H2AX foci.The number of existing PML-NBs per nucleus declined with age, while the number of ?H2AX foci increased with age. There was a non-significant trend that in vivo irradiation increased the number of PML-NBs in cells of young study participants, while in older individuals PML-NBs tended to decrease. It can be assumed that PML-NBs decrease in number during the process of aging.The findings suggest that there is a dysfunctional PML-NBs stress response in aged cells.
EVALuna2:18179